2004
DOI: 10.1016/j.jep.2004.02.011
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antiplasmodial activity of medicinal plants native to or naturalised in South Africa

Abstract: The increasing prevalence and distribution of malaria has been attributed to a number of factors, one of them being the emergence and spread of drug resistant parasites. Efforts are now being directed towards the discovery and development of new chemically diverse antimalarial agents. The present study reports on the in vitro antiplasmodial activity of 134 plant taxa native to or naturalised in South Africa, representing 54 families, which were selected semi-quantitatively using weighted criteria. The plant ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
289
3
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 461 publications
(319 citation statements)
references
References 28 publications
19
289
3
8
Order By: Relevance
“…An ethanol leaf extract from D. cinerea showed no activity at the highest concentration (5 μg/ml) tested (Atindehou, 2004). Results from the current study do not support the relatively low antiplasmodial activity (IC50 ≥ 10 μg/ml) reported previously for R. caffra (Clarkson et al, 2004). Boyom et al (2011) reported on the potency of methanol leaf and stem extracts of X. parviflora from Cameroon.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…An ethanol leaf extract from D. cinerea showed no activity at the highest concentration (5 μg/ml) tested (Atindehou, 2004). Results from the current study do not support the relatively low antiplasmodial activity (IC50 ≥ 10 μg/ml) reported previously for R. caffra (Clarkson et al, 2004). Boyom et al (2011) reported on the potency of methanol leaf and stem extracts of X. parviflora from Cameroon.…”
Section: Resultscontrasting
confidence: 99%
“…Chloroquine-sensitive strain of Although Albizia species are well documented for their strong in vitro as well as in vivo antimalarial activities (Samoylenko et al, 2009), reports on A. versicolor are lacking. Clarkson et al (2004) detected a weak antiplasmodial activity (IC50 = 38 μg/ml) in the dichloromethane root extract C. tomentosa, which is relatively low compared to the results (IC50 = 2.19 μg/ml) found in this study. An ethanol leaf extract from D. cinerea showed no activity at the highest concentration (5 μg/ml) tested (Atindehou, 2004).…”
Section: Resultscontrasting
confidence: 98%
See 1 more Smart Citation
“…The subset of eight plant species investigated in this study was selected as follows: Plants were first and foremost chosen for being used traditionally for either malaria or fever treatment as documented in ethnobotanical studies (Alam et al, 2012;Clarkson et al, 2004;Van Wyk, 2008; Table 1). From the ethnobotanical set, plants were selected based on two parallel criteria: 1) previous reports of either good or moderate activity against the intraerythrocytic asexual parasites of P. falciparum parasites (IC 50 ≤10 µg/ml -good;…”
Section: Plant Selection Collection and Crude Acetone Extract Preparmentioning
confidence: 99%
“…The three plant species investigated namely, L. leonurus, L. leonurus ex Hort and Olea europaea (Oleaceae) were selected based on previously reported activity against the intraerythrocytic asexual parasites of P. falciparum (Table 1) (Clarkson et al, 2004). Khaya anthotheca (Meliaceae) was selected as the Meliaceae family, has been shown to produce limonoids that are potent against gametocytes (Jones et al, 1994;Lucantoni et al, 2010;Yerbanga et al, 2014).…”
Section: Plant Selection Collection and Extractionmentioning
confidence: 99%